Developing a Comprehensive Assessment Tool for Elementary Students’ Scientific Literacy - Hafiziani Eka Putri; Fitri Nuraeni; Nenden Permas Hikmatunisa; Ravy Hun; Salis Elmadani (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractÂ Scientific literacy embodies the essential scientific knowledge and skills that students require for comprehending and applying scientific concepts in their daily lives. This study aimed to design an assessment tool for gauging elementary school students' scientific literacy. Adopting the Research and Development (R&D) approach, this study incorporates a 3D (Define, Design, and Develop) framework. The scientific literacy indicators devised encompass the ability to explain phenomena scientifically, evaluate and design scientific inquiry, and interpret data and evidence scientifically. The outcome of this research manifests as a Scientific Literacy Instrument comprising six open-ended questions accompanied by alternative answer schemes. The appropriateness of all items demonstrates a moderate level of validity. The reliability of the test items indicates a commendable degree of consistency. The complexity of the questions ranges from moderate to challenging. The discriminating power of each item indicates a noteworthy level of differentiation. Thus, the scientific literacy assessment tool formulated in this study serves as an effective means of evaluating students' scientific literacy in the context of elementary school science education.Keywords: instrument, scientific literacy, science learning.AbstrakLiterasi sains merupakan pengetahuan dan keterampilan ilmiah yang perlu dipahami dan diterapkan siswa dalam kehidupan sehari-hari. Tujuan penelitian ini adalah untuk mengembangkan instrumen kemampuan literasi sains yang dapat digunakan pendidik untuk mengukur kemampuan literasi sains siswa dalam pembelajaran sains di sekolah dasar. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan desain 3D (Define, Design, dan Develop). Indikator literasi sains yang dikembangkan antara lain menjelaskan fenomena, mengevaluasi dan merancang pertanyaan, serta menafsirkan data dan bukti secara ilmiah. Penelitian ini menghasilkan Instrumen Kemampuan Literasi Sains yang terdiri dari 6 soal essay dengan alternatif kunci jawaban. Hasil perhitungan validitas seluruh item mempunyai interpretasi sedang. Reliabilitas soal tes mempunyai interpretasi yang baik. Tingkat kesukaran butir soal interpretasi sedang hingga sulit. Daya pembeda tiap item diartikan dari baik sampai sangat baik. Dengan demikian instrumen tes kemampuan literasi sains yang dikembangkan dalam penelitian ini dapat digunakan sebagai instrumen untuk mengukur kemampuan literasi sains siswa di sekolah dasar.Kata kunci: instrumen, literasi sains, pembelajaran sains.